Bangkang papel sa dagat ng apoy - Reyes, Edgardo; Estrada, Joseph; Enriquez, Laarni; Diaz, Paquito; Cine Suerte (Firm). ([Place of production not identified] Cine Suerte, 1984)
Erap plays the role of a factory worker who decides to form a labor union after seeing the injustices being committed by the owners of the factory. However, the owners form a company union composed of hired hands who are not workers but gangsters. With the existence of two unions, trouble brews but the group of Erap triumphs in the end.
Music by Ernani Cuenca; cinematography by Fredy Conde.
Joseph Estrada, Laarni Enriquez, Paquito Diaz.
DVD
In Tagalog
Keywords: Drama